Workforce diversity and organizational performance: a study of IT industry in India. Issue 2 (13th February 2017) - Kundu, Subhash C.; Mor, Archana
Abstract : Purpose: The purpose of this paper is to examine the relationship between employee perceptions of diversity (i.e. significance of diversity and diversity management, and value of diversity practices employed) and perceived organizational performance. It also attempts to examine whether the perceptions of diversity vary among employees from different diversity backgrounds (i.e. across gender and categories) in Indian IT industry. Design/methodology/approach: Primary data based on 402 respondents were analysed using statistical tools like factor analysis, correlations, analysis of variance, means, grand means, and regression. Findings: Results indicated that employees irrespective of their diversity backgrounds positively acknowledged diversity and diversity management. However, limited but significant differences were observed among employee perceptions regarding valuing the diversity practices employed based on their diversity backgrounds. Further, employees' perception of promotion of gender diversity was found to be positively related to perceived organizational performance. Research limitations/implications: This paper relied on self-report surveys for data collection. Future studies should collect data using multiple methods to avoid common-method bias. As the sample was drawn from India, specifically from IT industry, the conclusions may not be generalized to other industries. Future studies may be conducted across industries covering different cultural settings. Practical implications: Implications are first, that, in addition to investing in initiatives for promoting diversity, especially gender diversity, organizations need to ensure positive perceptibility of these initiatives by employees. Second, to foster acceptance and effectiveness of gender/diversity initiatives in organizations, managers need to ensure men and majority group employees are part of these initiatives. Third, IT industry needs to reassess their hiring strategies and should design diversity programmes with goals in mind, if not quotas, to hire and retain diverse employees to explore their potential contribution. Originality/value: Inclusion of employees of Indian IT industry of different categories will definitely add value to the existing knowledge on diversity, management theory, and practice.